Clinical response to chemotherapy in non-small cell lung carcinoma patients - Narukurthi, Ravi Kiran; Krishna, Nallamothu Murali; Mounika, Jetty; Chandra, T. Jaya (International Journal of Research in Medical Sciences, 2019)
Background: Lung carcinoma is the most common. With this, a study was conducted to assess the clinical profile of Non-small cell lung carcinoma (NSCLC) and also to evaluate the response to chemotherapy in various stages of NSCLC. Methods: It was a prospective study. All the clinically confirmed cases with NSCLC were taken into consideration. Clinical staging was done, diagnosis was confirmed by histopathological findings. Treatment was given depending on the stage of carcinoma. Patients were evaluated before each cycle of chemotherapy for any progression of disease. Pathological response was evaluated after completion of 6 cycles of chemotherapy. Chi square test was used to find the statistical significance; p<0.05 was considered statistically significant. Results: Total 153 patients admitted to oncology wing were taken to the study, with mean age 59.07±10.618 years, 2.6 male female ratio. In this 73% were in stage III and the remaining in stage IV NSCLC. Majority (56.10%) of the study subjects in stage III NSCLC showed partial response, Majority (68%) of the subjects in stage IV NSCLC showed partial response; the difference was Statistically significant (p<0.05). Conclusions: NSCLS is common in older people with male dominance due to habits.